Microstructure and Mechanical Properties of 45 vol.% SiCp/7075Al Composite. Issue 9 (September 2015) - Xiu, Ziyang; Yang, Wenshu; Dong, Ronghua; Hussain, Murid; Jiang, Longtao; Liu, YongXing; Wu, Gaohui
<x xml:space="preserve">Abstract</x> Microstructure and mechanical behavior of high volume content SiCp/7xxxAl composites have not been explored yet. Therefore, in the present work, 45 vol.% SiCp/7075Al composite has been prepared by pressure infiltration method. High density dislocations were found around SiC/Al interface in SiCp/7075Al composite after water-quenching and aging treatment. Fine dispersed nano-η′ phases were observed after the aging treatment. Adverse to other SiCp/Al composites prepared by the pressure infiltration method, an interface layer was observed between SiC particles and Al matrix. Furthermore, high-resolution transmission electron microscopy (HRTEM) observation indicated that this interface layer was coherent/semi-coherent with that of the SiC particles. 45 vol.% SiCp/7075Al composite demonstrated high tensile strength (630 MPa) and micro-ductility. Compared to aged SiCp/2024Al composite, the aged SiCp/7075Al composite showed an increase of about 200% in the tensile strain and 90% in the tensile strength, respectively. It is speculated that nano-η′ phases in the Al matrix significantly contributed to the strengthening effect while the interface layer between SiC and Al matrix might be beneficial to the strength and plasticity of SiCp/7075Al composite.